IMPROVING GRADE X STUDENTS’ SPEAKING COMPETENCE IN REPORTING A PROCEDURE TEXT BY USING VIDEO - Siti Aulia Febriyanti; Tina Mariany Arifin (Universitas Negeri Medan, 2014)
This study was carried out to discover students’ speaking competence in reporting a procedure text by using video. It was a Classroom Action Research (CAR). The subject was students of Grade X, State Senior High School (Sekolah Menengah Atas Negeri: SMAN) 5 Binjai, which consisted of 42 students. The research was conducted in two cycles and each cycle consisted of three meetings. The instruments used to collect the data were speaking tests as quantitative data and Observation Sheet, Interview, Questionnaire, and Diary Notes as qualitative data. The results of the speaking tests showed that the students’ score improved in every test. The mean of the students’ score in Orientation test was 51.17, the mean of the students’ score in Cycle I was 69.05, and the mean in Cycle II was 80.31. The mean score in Cycle II was the highest, so it can be said that the students’ speaking competence improved from 51.17 to 80.31. Based on the Observation Sheet, Interview, Questionnaire, and Diary Notes, it was found that the teaching-learning process ran well. The findings of the study indicate that using Video significantly improved the students’ speaking competence. So, English teachers are suggested to use Video in order to improve the students’ speaking competence in reporting a procedure text.